(untitled) (Journal of Student Affairs in Africa, 2021)
In this article we argue for a socio-political conception of space in order to show how conceptualisations of space can provide conceptual tools in the reframing of policy and designing of policy interventions in pursuit of higher education transformation goals. In keeping with Lefebvre and others, we conceptualise space as a co-producer of social relations with agentic capability in the transformation of higher education. Using this understanding of space as a conceptual framework, we analyse four national cornerstone policy documents on higher education transformation in South Africa. We find that space is almost consistently conceived of only as an object in transformation - be it with respect to macro policy on mergers to reconfigure the apartheid spatial landscape of higher education, or with respect to discriminatory institutional cultures and the need to create secure and safe campus environments. Since the landmark White Paper on Higher Education of 1997, it is only the most recent policy document we analyse, the Draft National Plan for Post-school Education and Training of 2017, which blurs the lines between the social ills affecting higher education, the student experience and student academic performance, and different functions of space. We conclude by introducing the conceptual tool of spatial types as an opening gambit for a research agenda that aims to explore the organisation of space in higher education institutions to identify the underlying rules that govern their social nature and promote conceptualisations of social space in the reframing and design of policy that respond to calls for the creation of transformed and ’decolonised’ higher education, as heard in studentmovement campaigns in 2015/16.